2009
DOI: 10.1080/00016350902992602
|View full text |Cite
|
Sign up to set email alerts
|

Colony morphologies, species, and biotypes of yeasts from thrush and denture stomatitis

Abstract: A diversity of species and phenotypes was found among the yeasts in thrush and denture stomatitis. Candidal commensals were predominant in thrush and denture stomatitis, but the observation of divergent Candida species and biotypes, constituting 23% of all the yeast isolates, should not be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Multiple colony morphologies may be associated with diverse oral Candida phenotypes in patients with thrush and denture‐related stomatitis 41 . In the present study, denture adhesives induced several C. albicans colony phenotypes that might be associated with virulence and adaptation processes 41 . Furthermore, microscopic observations revealed that several denture adhesives can induce vacuolisation of yeast cells.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Multiple colony morphologies may be associated with diverse oral Candida phenotypes in patients with thrush and denture‐related stomatitis 41 . In the present study, denture adhesives induced several C. albicans colony phenotypes that might be associated with virulence and adaptation processes 41 . Furthermore, microscopic observations revealed that several denture adhesives can induce vacuolisation of yeast cells.…”
Section: Discussionsupporting
confidence: 51%
“…Such phenotypic switching involves reversible and heritable switching between alternative cellular phenotypes, often distinguished by differences in microscopic and macroscopic morphology 40 . Multiple colony morphologies may be associated with diverse oral Candida phenotypes in patients with thrush and denture-related stomatitis 41 . In the present study, denture adhesives induced several C. albicans colony phenotypes that might be associated with virulence and adaptation processes 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been hypothesized that the hyphal form of C. albicans can better adhere to and penetrate fissures on denture surfaces and is thus more invasive to the oral mucosa (Fig 5). 5,6 Song et al 59 recently characterized yeast isolates from patients with denture stomatitis; C. albicans was the predominant species. The authors noted that yeasts that colonized the dentures and mucosa of stomatitis patients formed colonies with diverse morphologies, while the same yeast species when present in healthy denture wearers formed colonies with smooth morphology 59 .…”
Section: Resultsmentioning
confidence: 99%
“… 5,6 Song et al 59 recently characterized yeast isolates from patients with denture stomatitis; C. albicans was the predominant species. The authors noted that yeasts that colonized the dentures and mucosa of stomatitis patients formed colonies with diverse morphologies, while the same yeast species when present in healthy denture wearers formed colonies with smooth morphology 59 . Bilhan et al reported a significantly higher presence of C. albicans hyphae among patients with denture stomatitis compared to healthy denture users without palatal inflammation 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Essas espécies, porém, estão presentes em menor prevalência quando comparadas a C. albicans, não apresentando, segundo Odds (1997), um papel patológico relevante para a doença. Além da prevalência da forma hifal ser detectada na mucosa de pacientes com estomatite protética (WEBB et al, 1998;SONG et al, 2009), também há evidências de que C. albicans penetra e adere nas fissuras das superfícies de resina das próteses dentárias (WEBB et al, 1998;RAMAGE et al, 2004;GUSMÃO et al, 2011). …”
Section: Estomatite Protéticaunclassified